Specificity Of Socio-Demographic Forecasting For The Russian Society - S. Chikaeva, Karina (2019)
The study of demographic processes in Russian society involves socio-demographic forecasts. The article pays attention to the theoretical understanding of the category "demographic projection", it describes four classifications of demographic projections; It presents a practical synthesis of the currently existing socio-demographic forecasts for the Russian society in the medium term. The demographic situation in Russia is assessed as critical because Russian society has to recognize the fact of the birth crisis. The article discusses the causes of the Russian demographic crisis, presents statistical data on demographic indicators of births and deaths, and describes three groups of scenarios for medium-term demographic forecasting.